Penambahan Ekstrak Daun Kelor (Moringa Oleifera) dalam Air Minum Terhadap Performa Broiler - Mihrani, Mihrani; Yulianti, Sri (Indonesian Journal of Fundamental Sciences, 2024)
Abstract. This study aims to determine the performance of broilers with the addition of Moringa (Moringa Oleifera) leaf extract. This study was conducted in April 2022,  Romang Lompoa Village, Bontomarannu District, Gowa Regency, South Sulawesi Province. This study was carried out by using a Completely Randomized Design (CRD) with 46 broilers with 4 treatments and 4 replications, each replication consisting of 3 chickens. Each experimental design sample used in this study is P0 = Without Moringa leaf extract (Control), P1 = Drinking water with 3% Moringa leaf extract in 1 liter of water, P2 = Drinking water with 6% Moringa leaf extract in 1 liter of water, P3 = Drinking water with 3% Moringa leaf extract in 1 liter of water. The variables observed were feed consumption, weight gain, feed conversion, and drinking water consumption. The results of this study indicate that broiler performance with adding Moringa oleifera leaf extract can affect feed consumption, weight gain, and drinking water consumption. There was a significant difference in feed consumption in treatment P1 with a concentration of 3% (30 ml), weight gain occurred in treatment P2 with a concentration of 6% (60 ml), and in drinking water consumption there was a significant difference in treatment P1 with a concentration of 3% ( 30 ml).